Construction of circRNA-miRNA-mRNA Network for Exploring Underlying Mechanisms of Lubrication Disorder - Cong, Shengnan; Li, Jinlong; Zhang, Jingjing; Feng, Jingyi; Zhang, Aixia; Pan, Lianjun; Ma, Jiehua (Frontiers in Cell and Developmental Biology, 2021)
Lubrication disorder is a common health issue that manifests as insufficient sexual arousal at the beginning of sex. It often causes physical and psychological distress. However, there are few studies on lubrication disorder, and the complexity of circular RNA (circRNA) and the related competing endogenous RNA (ceRNA) network in lubrication disorder is still poorly known. Therefore, this study aims to build a regulatory circRNA-micro (mi)RNA-mRNA network and explore potential molecular markers of lubrication disorder. In the study, 12 subjects were recruited, including 6 in the lubrication disorder group and 6 in the normal control group. RNA sequencing was exploited to identify the expression profiles of circRNA, miRNA and mRNA between two groups, and then to construct the circRNA-miRNA-mRNA networks. The enrichment analyses of the differentially expressed (DE)-mRNAs were examined via Gene Set Enrichment Analysis (GSEA). Furthermore, the expression level and interactions among circRNA, miRNA, and mRNA were validated using real-time quantitative polymerase chain reaction (RT-qPCR) and dual-luciferase reporter assays. In the results, 73 circRNAs, 287 miRNAs, and 354 target mRNAs were differentially expressed between two groups when taking | Log2 (fold change)| > 1 and P-value < 0.05 as criteria, and then the results of GSEA revealed that DE-mRNAs were linked with “vascular smooth muscle contraction,” “aldosterone regulated sodium reabsorption,” “calcium signaling pathway,” etc. 19 target relationships among 5 circRNAs, 4 miRNAs, and 7 mRNAs were found and constructed the ceRNA network. Among them, hsa-miR-212-5p and hsa-miR-874-3p were demonstrated to be related to the occurrence of lubrication disorder. Eventually, consistent with sequencing, RT-qPCR showed that hsa_circ_0026782 and ASB2 were upregulated while hsa-miR-874-3p was downregulated, and dual-luciferase reporter assays confirmed the interactions among them. In summary, the findings indicate that the circRNA-miRNA-mRNA regulatory network is presented in lubrication disorder, and ulteriorly provide a deeper understanding of the specific regulatory mechanism of lubrication disorder from the perspective of the circRNA-miRNA-mRNA network.